Family characteristics of students with dyslexia and access to higher education - Λουάρη, Μαρίνα (Education Sciences, 2023)
Students with dyslexia often have low academic achievement and a lower success rate in entrance exams to higher education than typically developing students. The socio-economic characteristics of the family are related to the cognitive development of children, but it has not been investigated whether these characteristics affect the educational process of students with dyslexia. The purpose of this study was to investigate the characteristics of students’ with dyslexia family and how they affect the likelihood of continuing their studies in higher education. 74 people with a diagnosis of dyslexia and average aged 19.5 years participated. A questionnaire was designed for data collection and additional data were collected through an interview.The analysis of the data showed that the family environment is supportive and more supportive seems to be parents of university education as opposed to those who have only completed compulsory education, as their children have lower achievement and lower success rate in the entrance exams for university.